148k views
1 vote
Find f(x) + g(x)

F(x)= 2x^2 - 4x-3
and
g(x)=2x^2+16

A) 4x^2-4x-19
B) 4x^2-4x-13
C) 4x^2-4x+13
D) -4x-19

User Hyosun
by
5.8k points

2 Answers

6 votes

Answer:

C

Explanation:

f(x) + g(x)

= 2x² - 4x - 3 + 2x² + 16 ← collect like terms

= (2x² + 2x² ) - 4x + (- 3 + 16)

= 4x² - 4x + 13 → C

User Vipin Kumar
by
5.1k points
0 votes

The answer is option no B.

User Yhn
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.